Study of the Synthesis of Zirconia Powder from Zircon Sand obtained from Zircon Minerals Malaysia by Caustic Fusion Method - Istikamah Subuki; Mimi Fazzlinda Mohsin; Muhammad Hussain Ismail; Fazira Suriani Mohamed Fadzil (Universitas Gadjah Mada, 2020)
The zircon powder from Zircon Minerals Malaysia is a pure premium grade zircon sand milled 1.5 µm that contain ZrSiO4, ZrO2, HfO2, SiO2, Al2O3, TiO2, and Fe2O3. The monoclinic zirconia powders were synthesized from the zircon sand of Zircon Minerals Malaysia, by caustic fusion method at calcination temperatures between 500 °C to 800 °C. The as-synthesized zirconia was characterized through X-Ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric and differential thermal analysis (TG-DTA), and X-Ray fluorescence (XRF) techniques. The XRD results show two monoclinic phases of microcrystalline zirconia. Zirconia that was calcined at 600 °C obtained the highest value of ZrO2, which was 54.48%; followed by zirconia calcined at 700 °C, 800 °C, and 500 °C, which obtained the ZrO2 values of 53.58%, 52.41%, and 51.53%, respectively, based on the XRF analysis. As-synthesized zirconia showed monoclinic phases where the surface areas were 0.0635 m2/g, 0.135 m2/g, 0.0268 m2/g, and 0.0288 m2/g, for zirconia calcined at temperatures of 500 °C, 600 °C, 700 °C, and 800 °C, respectively. The surface structure of the powder that had been calcined at 600 C showed similarities with the commercial zirconia. The similarities of the synthesized zirconia and commercial zirconia showed that the zirconia powder could be synthesized using zircon sand by caustic fusion method, even though the content of zirconia was lower compared to that of the commercial zirconia powder.